Industria 4.0 y sostenibilidad: evaluación del compromiso organizacional con la agenda 2030 desde un enfoque bibliométrico. - Liarte-Vejrup, Nicolás; Bermúdez-González, Guillermo José; Álvarez-Nobell, Alejandro (Universidad Blas Pascal, 2024)
Sustainability offers multiple opportunities for companies wishing to innovate and develop triple-impact stakeholder engagement strategies, particularly the so-called Industry 4.0, a new phase of the industrial revolution based on interconnectivity, machine learning and real-time data. This paper is a bibliometric study that aims to put into perspective the contribution of Industry 4.0 and its contribution to the 2030 agenda.
Industry 4.0 and sustainability: assessing organizational commitment to the 2030 agenda from a bibliometric approach
Keywords: Información de sostenibilidad; Evaluación de impacto ambiental; Industria - Aspectos ambientales; Industry 4.0; Sustainability; Agenda 2030; SDGs; Impact assessment